A Review of the Blueberry Maggot Fly (Diptera: Tephritidae). (13th June 2015) - Rodriguez-Saona, Cesar; Vincent, Charles; Polk, Dean; Drummond, Francis A.
Abstract : Native to North America, the blueberry maggot fly, Rhagoletis mendax Curran (Diptera: Tephritidae), has historically been considered one of the most important insect pests of commercially grown highbush and lowbush blueberries in many parts of the northeastern and north central United States and Canada. Larval infestation results in unmarketable berries owing to a zero-tolerance policy enforced by quarantine regulations for exporting berries to countries outside the United States. To keep berries free from larvae, growers need to maintain an intensive management program that is based mainly on chemical control targeted at adults. Blueberry maggot flies have been largely managed by the use of broad-spectrum insecticides, including organophosphates and carbamates; however, restricted use of these old chemistries has resulted in increased use of "reduced-risk" neonicotinoids. Integrated pest management programs for blueberry maggot include the use of monitoring tools such as Pherocon-AM sticky traps, site-specific insecticide applications, border sprays, and use of reduced-risk insecticides. The pest status of the blueberry maggot fly in blueberries has changed recently due to the invasion into the continental United States of the spotted wing drosophila, Drosophila suzukii Matsumura, which has now become the main target of insecticide applications, replacing the blueberry maggot. This new invasive pest has disrupted integrated pest management programs implemented for blueberry maggot. The present review describes the biology, ecology, crop injury, monitoring tools, and control strategies currently used for blueberry maggot in blueberries, as well as provide a perspective on its present and potential future pest status.